Dynamic Changes of The Brain Substances Metabolism in Experimental Peritonitis - I. KARİMOV and B.D. BABADJANOV and B. B. SAFAYEV and O. R. TESHAYEV and YU. ERGASHEV (Turkish Journal of Gastroenterology, 2020)
-